(NmUZYKA I PO\TI^ESKOE SLOWO(B. (NiNTONACIQ kOMPOZICIQ(B.s (NmUZYKALXNAQ LITERATURAs - (Nw(B. (NwASINA gROSSMANs ((NmOSKWAs (NmUZYKAs, 1978)
(NkNIGA w(B. (Na(B. (NwASINOJ GRUSSMAN SOSTOIT IZ (B3-(N^ASTEJ(B.s
Keywords: (NmUZYKALXNOE LITERATURAs